(untitled) (Periphērica, 2020)
Blue and Not So Pink (2012), created by Miguel Ferrari as director and screenwriter, received innumerable positive and negative critiques. In spite of the negative evaluations, the film managed to become a great box office success in Venezuela and in 2013 obtained the Goya Award for the best Spanish American film. This study will analyze the film’s most significant themes; that is, that the consideration of human diversity as an element should be accepted in our societies, the possibility of giving voice to persons who suffer discrimination and the issue of self-acceptance. The notion that the film proposes that there should be other types of families in our societies will be considered: families with gay parents, those with only one parent, and therefore, families that are formed with no blood relationship whatsoever. The trajectory of the main characters within parameters that are juxtaposed and, at the same time, complement each other will be observed—the private and public world, the social sphere and the familial one. Consequently, the transformation that occursin the family unit to include more unbiased parental rights for homosexuals and transexuals in the formation of a new kind of family core will likewise be examined. By way of conclusion, it will be observed how the musical diversity of the film is developed intradiegetically to support gender diversity, as well as an examination of the concept of gender within heterocentric society and the way in which relationships of homosexual couples and transgender couples challenge patriarchal society and the dichotomous, binary system it adopted.